2009
DOI: 10.1007/s10661-009-1183-3
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex and spatial dependent variations in heavy metals levels in the Glaucous Gulls (Larus hyperboreus) from the Bjørnøya and Jan Mayen, Arctic

Abstract: Heavy metals (Cd, Cu, Fe, Mn and Zn) concentrations were determined in different tissues (muscle, kidney, liver, brain, gonads, heart and feathers) of Glaucous Gulls (Larus hyperboreus) from Bjørnøya and Jan Mayen. The age and spatial dependent variations in heavy metals were quantified and interpreted in view of the three chemometric techniques, i.e. non-parametric Mann-Whitney U test, redundancy gradient analysis and detrended correspondence analysis. The Glaucous Gulls from Bjørnøya contained significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 24 publications
1
7
3
Order By: Relevance
“…Kim et al (1998) present data with similar distribution and, in a general way, within the same orders of magnitude as the present work. Elevated Cu variation in this tissue might be linked to body condition, as suggested by Malinga et al (2010). These authors also suggested that the variation of Cu concentrations could be due to different stages of development of the gonads, which was visually confirmed in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Kim et al (1998) present data with similar distribution and, in a general way, within the same orders of magnitude as the present work. Elevated Cu variation in this tissue might be linked to body condition, as suggested by Malinga et al (2010). These authors also suggested that the variation of Cu concentrations could be due to different stages of development of the gonads, which was visually confirmed in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…There are few studies of the levels of heavy metals in the brain tissue of birds. Compared to other studies, the level of heavy metals in brain tissues in this study were higher than other studies in other parts of the world, including Zator and Milicz, Poland (Binkowski and Sawicka-Kapusta 2015), wetland in north western Poland (Kalisińska et al 2004), Gdansk Bay Baltic Sea, Poland (Szefer and Falandysz 1987b) Nilgiris, Tamil Nadu, India (Jayakumar and Muralidharan 2011), lagoon of Marano, Italy (Leonzio et al 1986), BjØrØya and Jan Mayen Artic (Malinga et al 2010), Pomeranian Bay, Poland (Kalisińska and Szuberla 1996).…”
Section: Variation Among Organscontrasting
confidence: 86%
“…There are few studies of the levels of heavy metals in the brain tissue of birds. Compared to other studies, the level of heavy metals in brain tissues in this study were higher than other studies in other parts of the world, including Zator and Milicz, Poland (Binkowski and Sawicka-Kapusta 2015), a wetland in Northwestern Poland (Kalisińska et al 2004), Gdansk Bay Baltic Sea, Poland (Szefer and Falandysz 1987b), Nilgiris, Tamil Nadu, India (Jayakumar and Muralidharan 2011), a lagoon of Marano, Italy (Leonzio et al 1986), BjØrØya and Jan Mayen Artic (Malinga et al 2010), and Pomeranian Bay, Poland (Kalisińska and Szuberla 1996).…”
Section: Variation Among Organscontrasting
confidence: 83%